Complementarity between multilateral lending and private flows to Developing countries : some empirical results - Ratha, Dilip K. (Policy research working paper, 2001)
Even though multilateral loans may have behaved countercyclically with respect to private flows to Developing countries in the short term, these flows tended to complement private flows in the medium term by signaling, and often fostering, a better investment environment in the borrowing country